Լոկուս կոնտրոլը և վարքի հիմքում ընկած դրդապատճառները - Գանջի Ասքարի Ասղարի (ՀՀ ԳԱԱ հրատ.)
In this study the locus of control has been used as a framework for recognizing the basic causes of behavior. The major concern of this study is to find out “who and what” controls the behavior in individuals.
Keywords: Psychology